Pengaruh Kualitas Pelayanan terhadap Kepuasan Masyarakat Dalam Penerbitan Surat Keterangan Catatan Kepolisian (SKCK) - Puspita, Rastra Wahyu; Fajriana, Icha (MDP Student Conference, 2024)
The aim of this research is to examine and analyze the relationship between service quality and public satisfaction in the issuance of police record certificates (SKCK). This research uses an associative quantitative approach. This research uses two types of data sources, namely primary data sources and secondary data sources. This research surveyed 96 respondents by distributing questionnaires directly to the community who made SKCK at the South Sumatra Police SPKT Office. The sampling technique used was purposive sampling. Research data was analyzed using multiple linear regression analysis. The research results show that service quality has a significant effect on public satisfaction in issuing police record certificates (SKCK).